PERAN STF UIN JAKARTA TERHADAP TINDAKAN PREVENTIF PUTUS KULIAH DALAM PERSPEKTIF KOMUNIKASI PEMBANGUNAN - Nisa, Ishmatun; Bakti, Andi M. Faisal; Hermansah, Tantan; Fanshoby, Muhammad (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
Poverty is one of the factors causing dropouts that must be solved by the government. Preventive actions to dropouts carried out by the government have not been comprehensive. Social Trust Fund (STF) UIN Jakarta improves the quality of education by solving students' economic problems through educational scholarships. The purpose of this study are to analyze the role of STF UIN Jakarta in preventing dropouts from the perspective of development communication, explain the STF UIN Jakarta diffusion model for preventing actions against dropouts, and determine the purpose of STF UIN Jakarta using a participatory model for preventing dropouts. STF UIN Jakarta is one of the institutions in UIN Jakarta controlling preventive dropouts. The STF UIN Jakarta program help students to solve their financial problems of education through scholarships, Charity Stores, Bailout Funds, Bungkesmas, Entrepreneurial Waqf Houses, and Waqf Endowment Funds. In this study, writer used a book from Jan Servaes, Communication for Development and Social Change (2008: 202-219). The theory used is Development Communication. The role of Development Communication carried out by STF UIN Jakarta is the publication of information such as writing, photos and videos through Socialtrustfund UIN JKT YouTube content, Twitter @STF_Uinjkt, Instagram @stfuinjkt, and Social Trust Fund UIN Jakarta Facebook account. STF UIN Jakarta involves the participation from all parties. STF UIN Jakarta prevents college dropouts through scholarship programs which funded by internal and external investors. STF UIN Jakarta has innovative programs to achieve social welfare.